The Importance Of Using Financial Failure Prediction Models As Analytical Procedures To Verify The True Financial Position Of The Company - Hachi ,Faiza Oumelkheir (جامعة الوادي University of Eloued, 2024)
Through our paper, we seek to highlight the impact of using the Financial Deterioration Prediction Methods (KIDA-SHERROD-ALTMAN) to demonstrate the true status of the enterprise, which is a service for users of the financial statements of the enterprise, and accordingly the study was divided into two parts, one in which the definitions of the basic variables were addressed, while the other part included the application of the aforementioned curriculum at the level of pharmaceutical manufacturerHIKMA for the chain time2017-2023. Our study found both Sherrod and Altman's competence and ability to spare the auditor from potential detection risks by giving them a very rough picture of the real financial situation of the institution under examination.
Keywords: Professional Opinion; Auditor; Methods of Financial Decline